2021
DOI: 10.3390/molecules26040848
|View full text |Cite
|
Sign up to set email alerts
|

Polyphyllin D Shows Anticancer Effect through a Selective Inhibition of Src Homology Region 2-Containing Protein Tyrosine Phosphatase-2 (SHP2)

Abstract: Natural products have continued to offer tremendous opportunities for drug development, as they have long been used in traditional medicinal systems. SHP2 has served as an anticancer target. To identify novel SHP2 inhibitors with potential anticancer activity, we screened a library containing 658 natural products. Polyphyllin D was found to selectively inhibit SHP2 over SHP1, whereas two other identified compounds (echinocystic acid and oleanolic acid) demonstrated dual SHP1 and SHP2 inhibition. In a cell-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Zhou et al, 2021). Several active compounds of CL such as polyphyllin D, polyphyllin A, polyphyllin I, polyphyllin II, polyphyllin VI (PPVI), and polyphyllin VII were identified (Wang Q. et al, 2018;Pang et al, 2020;Teng et al, 2020;Ahmad et al, 2021;Kwon et al, 2021). Bioactive chemicals from CL for the treatment of inflammatory pain and the underlying mechanisms were not fully elucidated.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al, 2021). Several active compounds of CL such as polyphyllin D, polyphyllin A, polyphyllin I, polyphyllin II, polyphyllin VI (PPVI), and polyphyllin VII were identified (Wang Q. et al, 2018;Pang et al, 2020;Teng et al, 2020;Ahmad et al, 2021;Kwon et al, 2021). Bioactive chemicals from CL for the treatment of inflammatory pain and the underlying mechanisms were not fully elucidated.…”
Section: Figurementioning
confidence: 99%
“…Steroidal saponins, flavonoids, sugars, volatile oils, amino acids, trace minerals, etc., are among CL’s active constituents, mediating anti-tumor ( Tian et al, 2020 ), anti-infection ( Qiumin et al, 2017 ), organ-protecting ( Man et al, 2014 ), and anti-inflammatory effects ( Yan et al, 2021 ; Zhou et al, 2021 ). Several active compounds of CL such as polyphyllin D, polyphyllin A, polyphyllin I, polyphyllin II, polyphyllin VI (PPVI), and polyphyllin VII were identified ( Wang Q. et al, 2018 ; Pang et al, 2020 ; Teng et al, 2020 ; Ahmad et al, 2021 ; Kwon et al, 2021 ). Bioactive chemicals from CL for the treatment of inflammatory pain and the underlying mechanisms were not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Several druggable pockets in SHP2 include: (1) the conserved PTP active sites, (2) the “tunnel” allosteric site 1 at the C-SH2/PTP domain interface, (3) the “latch” allosteric site 2 at the N-SH2/PTP domain interface that is located approximately 20 Å away from the tunnel, (4) the “groove” allosteric site 3 at the N-SH2/PTP domain interface that resides on the opposite side of the tunnel site, and (5) the cryptic allosteric sites in PTP domain , (Figure ). On the basis of the inhibition mechanism, SHP2 inhibitors are classified into two types: orthosteric and allosteric inhibitors.…”
Section: Strategies Targeting Shp2 For Cancer Therapymentioning
confidence: 99%
“…[110,111] More interestingly, comparing with previous catalytic site inhibitors from natural products, several natural products have recently been identified as allosteric inhibitors of SHP2, in which Polyphyllin D (66, Figure 21) performed selectivity against other PTPs and promising inhibition on Jurkat cell viability with an IC 50 of 2.8 μM. [112] Enzyme kinetics tests and docking models showed that Polyphyllin D inhibited SHP2 by acting on allosteric "tunnels", which showed the potential of natural products to be developed as allosteric inhibitors. After allosteric drugs had solved the problem of druggability and selectivity, people gradually began to pay attention to the mutation of SHP2.…”
Section: Allosteric Inhibitors Interacting With Tunnel-like Sitementioning
confidence: 99%